Satellite Remote Sensing Algorithm Development to Estimate Total Suspended Sediment Concentration for Highly Turbid Waters of Western Australia - Dorij, Passang (Curtin University, 2017)
Satellite-based remote sensing of total suspended sediment (TSS) concentration is studied for highly turbid waters of northern Western Australia. A robust multi-sensor red band semi-analytic sediment model was developed for coastal waters, and the implications of using a wide range of sensors with different spatial resolutions were also explored. In addition, historical TSS models were critically compared, and the feasibility of the geostationary satellite sensor AHI was also explored with respect to mapping TSS.